Social and Economic Efficiency of system of Corporate Governance - Коваленко, О. В.; Голомб, В. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
In the article the definitions of «corporation», «corporate governance», «efficiency of corporate governance» are defined. It was found that the characteristic features of an effective system of corporate governance are honesty, transparency, accountability and responsibility. Corporate governance in Ukraine was analyzed and it was found that the weakness that prevents the formation of an effective system of corporate governance is the level of institutions that directly affect on property rights – corruption, the judiciary, professionalism and honesty of managers. The reasons of a low level of implementation of corporate governance standards in Ukraine are analyzed. The basic directions of formation of a new model of economic growth in Ukraine in the coming years are determined, namely the shift of much of the financial resources from primary industries to the development of the «new» economy based on innovation and knowledge, to the formation of competitive intangibles and intellectual capital. The necessity of increasing the role of human capital of innovation type was proved to contribute to the effectiveness of the social component of corporate governance and will provide employment, stimulate the formation segment of skilled labor; develop a system of training and retraining of workers, increase investment and innovation investments in human capital. It was established that the current state of the national economy requires a rethinking of existing problems and the formation of more adequate to modern conditions of managing the national system of corporate governance that takes into consideration a number of factors, the main ones are: the mentality of society; a national culture, political and economic situation, the level of technology and knowledge-intensive activities in foreign markets and the internationalization of business.